2017
DOI: 10.1093/mnras/stx1686
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the properties of the kilohertz quasi-periodic oscillations and spectral parameters in 4U 1636−53

Abstract: We investigate the relation between the parameters of the energy spectrum and the frequency and amplitude of the kilohertz quasi-periodic oscillations (kHz QPOs) in the low-mass X-ray binary 4U 1636−53. We fit the 3 − 180-keV spectrum of this source with a model that includes a thermal Comptonisation component. We show that the frequencies of both kHz QPOs follow the same relation as a function of the parameters of this spectral component, except for a systematic frequency shift, whereas the rms fractional amp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 47 publications
5
42
0
Order By: Relevance
“…Gilfanov et al (2003), proposed that the lower kHz QPO originates in a boundary layer close to the NS surface, and it is associated with Comptonisation, and de Avellar et al (2013) proposed that, regardless of the dynamical mechanism that explains the kHz QPO frequencies, the radiative mechanism that governs the timing properties of the lower and upper kHz QPOs should be different. Recently, Ribeiro et al (2017) showed that the frequency dependence of the fractional rms amplitude of the upper kHz QPO, although in general different from that of the lower kHz QPO, exhibits the same behaviour as that of the lower kHz QPO around certain QPO frequencies. The latter finding indicates that when the lower and upper kHz QPOs are (separately) observed within a certain QPO frequency range, their variability could be caused by the same radiative mechanism.…”
Section: The Size Of the Corona And The Rms Amplitude Of The Lower Anmentioning
confidence: 99%
See 4 more Smart Citations
“…Gilfanov et al (2003), proposed that the lower kHz QPO originates in a boundary layer close to the NS surface, and it is associated with Comptonisation, and de Avellar et al (2013) proposed that, regardless of the dynamical mechanism that explains the kHz QPO frequencies, the radiative mechanism that governs the timing properties of the lower and upper kHz QPOs should be different. Recently, Ribeiro et al (2017) showed that the frequency dependence of the fractional rms amplitude of the upper kHz QPO, although in general different from that of the lower kHz QPO, exhibits the same behaviour as that of the lower kHz QPO around certain QPO frequencies. The latter finding indicates that when the lower and upper kHz QPOs are (separately) observed within a certain QPO frequency range, their variability could be caused by the same radiative mechanism.…”
Section: The Size Of the Corona And The Rms Amplitude Of The Lower Anmentioning
confidence: 99%
“…For the cold-seed case model, Γ increases from around 1.5 at 570 Hz to around 2.2 at 860 Hz and then decreased to 1.7 at 920 Hz. In Figure 4 we plot the observed Γ values from Zhang et al (2017) and Ribeiro et al (2017) together with the predicted values of Γ, given the best-fitting values of kTe τT and their MCMC uncertainties. The values of Γ, alongside their propagated uncertainties, are given in Table 2.…”
Section: Fitting the Modelmentioning
confidence: 99%
See 3 more Smart Citations